2020
DOI: 10.21037/atm-20-3022a
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis-associated ovarian carcinomas: insights into pathogenesis, diagnostics, and therapeutic targets—a narrative review

Abstract: Endometriosis is a benign gynecologic condition affecting up to one woman out of ten of reproductive age. It is defined by the presence of endometrial-like tissue in localizations outside of the uterine cavity. It often causes symptoms such as chronic pain, most frequently associated with the menstrual cycle, and infertility, but may also be oligo-or asymptomatic. There is evidence that some ovarian carcinoma (OC) histotypes, mainly the ovarian clear cell (OCCC) and endometrioid (EnOC) carcinoma, may arise fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 156 publications
0
51
0
Order By: Relevance
“…Attempts to identify somatic mutations that lead to the development of endometriotic lesions proved that some cancer-driving genes are more frequently mutated in ovarian endometriosis [17,18]. Mutations in these genes: ARID1A, PIK3CA, KRAS, are also found in ovarian cancer that is associated with endometriosis [19]. However, the same genes have been found to be mutated in eutopic endometrium in women without endometriosis, leaving the question about their pathogenicity still unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to identify somatic mutations that lead to the development of endometriotic lesions proved that some cancer-driving genes are more frequently mutated in ovarian endometriosis [17,18]. Mutations in these genes: ARID1A, PIK3CA, KRAS, are also found in ovarian cancer that is associated with endometriosis [19]. However, the same genes have been found to be mutated in eutopic endometrium in women without endometriosis, leaving the question about their pathogenicity still unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, POI-related gene families and pathways, such as the Fas ligand ( FasL )-Fas pathway, nuclear factor-kappa B ( NF-κB ), inhibitory kappa B α ( IκBα ), interleukin-1 receptor-associated kinase ( IRAK1 ), and tumor necrosis factor receptor-associated factor 6 ( TRAF6 ), have been reported in humans [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have shown that endometriosis patients have signi cantly increased risk of ovarian cancer [12]. As a precancerous lesion, endometriosis is closely related to ovarian clear cell and endometrioid carcinomas.…”
Section: Discussionmentioning
confidence: 99%